2020
DOI: 10.1002/hrdq.21419
|View full text |Cite
|
Sign up to set email alerts
|

Team engagement in an executive human resource development program: A closed cohort model perspective

Abstract: This study explored team engagement of two cohorts who had different team experiences in an Executive HRD program. Despite the widespread use of the closed cohort model (CCM) in executive programs and the recognition that a CCM is a type of team, there is a dearth of research on team engagement in cohorts. For ease of reference, the cohorts have been dubbed Team X and Team Y. Two research questions guided the study: What factors facilitated team engagement in a closed cohort model? What factors hindered team e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Task cohesion is shown to be positively related to the engagement of team learning behaviours (Bossche et al, 2006). In contemporary literature, researchers have a growing consensus that the nuances of engagement in teams, such as their commitment towards a goal (Marks et al, 2001), are impacted by factors such as cohesion (Forsyth, 2021; Waight & Edwards, 2021). Behavioural interactions characterise task cohesion as evidence of commitment, unity and resolve to complete a task (Carron et al, 1985).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Task cohesion is shown to be positively related to the engagement of team learning behaviours (Bossche et al, 2006). In contemporary literature, researchers have a growing consensus that the nuances of engagement in teams, such as their commitment towards a goal (Marks et al, 2001), are impacted by factors such as cohesion (Forsyth, 2021; Waight & Edwards, 2021). Behavioural interactions characterise task cohesion as evidence of commitment, unity and resolve to complete a task (Carron et al, 1985).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Drawing on the job demands-resources (JD-R) theory (Bakker & Demerouti, 2014, 2017, van Woerkom et al (2016c) conceptualized organizational support for strengths use as a type of job resource that helps employees achieve their work-related goals and engage in activities. Previous research has shown that organizational and supervisor support for strengths use has positive impacts not only on employees' strengths use, but also on their attitudes, well-being, and performance (Goetz & Boehm, 2020;Meyers et al, 2019;van Woerkom et al, 2016bvan Woerkom et al, , 2016cWaight & Edwards, 2021).…”
Section: Introductionmentioning
confidence: 99%